Tantangan Struktural,Politik, dan Budaya dalam Mewujudkan Konstitusional "Mencerdaskan Kehidupan Bangsa" - Tirsha Julisty; Watini Watini; Murtini Murtini; Fuad Abdillah (Journal of Innovative and Creativity, 2026)
This research aims to identify and analyze the complex structural, political, and cultural challenges that hinder the achievement of the constitutional goal of "educating the life of the nation" (engraved in the Preamble to the 1945 Constitution) in Indonesia.The method used is qualitative descriptive, including literature studies, descriptive analysis, case studies, and phenomenology, by examining various literature and legal documents. Although the Reformation era has brought significant changes, such as the decentralization of government (as the antithesis of the centralization of the New Order) and the purification of the presidential system, these constitutional goals are still hampered. The findings as the main challenges include: Structural Challenges: Includes political/party oligarchy, corruption, weak legal system (ineffective), and political dominance as commander-in-chief. Political Challenges: Manifested through opportunistic and pragmatic political practices, high cost politics, identity politics, and the implementation of procedural democracy that is not followed by substantial democracy. Cultural Challenges: Includes low political awareness (political blindness), community apathy, group egoism, and potential for religious radicalism in educational institutions. These challenges result in a misalignment between the ideals of the constitution and the reality of the state, thus hampering systemic efforts to educate the nation. Therefore, strengthening Civic Education (PKn) which focuses on political intelligence, active participation, and instilling the values of Pancasila and constitutionalism is considered as an urgency to overcome this problem. Keywords: Educating the Life of the Nation, Constitutionalism, Political Oligarchy, Structural Challenges, Identity Politics, Civic Education, Procedural Democracy